2011
DOI: 10.1007/s00170-011-3718-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and evaluating suitable tasks for autonomous industrial mobile manipulators (AIMM)

Abstract: This paper investigates the application potential for the technology-push manufacturing technology (TPMT) autonomous industrial mobile manipulation (AIMM), in order to link the conceptual ideas (academia) to actual manufacturing requirements (industry). The approach is based on the proposed TPMT methodology in a comprehensive industrial case study. More than 566 manufacturing tasks have been analyzed according to three main application areas (logistics, assistance, and service) to find their suitability for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…A range of general industrial applications suitable for mobile manipulators have been identified through an extensive study in real-world production environments [45]. The scope of the study included the analysis of 566 industrial tasks, carried out by human workers, since the tasks were either too complex or low volume to justify automation solutions [45,46].…”
Section: Finding Skillsmentioning
confidence: 99%
“…A range of general industrial applications suitable for mobile manipulators have been identified through an extensive study in real-world production environments [45]. The scope of the study included the analysis of 566 industrial tasks, carried out by human workers, since the tasks were either too complex or low volume to justify automation solutions [45,46].…”
Section: Finding Skillsmentioning
confidence: 99%
“…In this paper, we utilize an Autonomous Industrial Mobile Manipulator (AIMM) [18,19], which combines the advantages of both mobile robot and industrial manipulators and owns great mobility, flexibility and functionality, to be the "adult" robot. By observing the pure image features from a 2D camera and leaming how to perform action in the corresponding state, the "adult" robot can accomplish the teaching task precisely.…”
Section: Reasoning Based On Observations and Uncertaintiesmentioning
confidence: 99%
“…After a thorough study of the possible applications where the robot could offer a better response and be more autonomous and efficient [26], a complex task was identified that supposes a new technological challenge and of great applicability in the industry.…”
Section: Automotive Use Casementioning
confidence: 99%